VGF nerve growth factor inducible is involved in retinal ganglion cells death induced by optic nerve crush. Issue 1 (December 2018) - Takeuchi, Hiroto; Inagaki, Satoshi; Morozumi, Wataru; Nakano, Yukimichi; Inoue, Yuki; Kuse, Yoshiki; Mizoguchi, Takahiro; Nakamura, Shinsuke; Funato, Michinori; Kaneko, Hideo; Hara, Hideaki; Shimazawa, Masamitsu
Abstract VGF nerve growth factor inducible (VGF) is a polypeptide that is induced by neurotrophic factors and is involved in neurite growth and neuroprotection. The mRNA of theVgf gene has been detected in the adult rat retina, however the roles played by VGF in the retina are still undetermined. Thus, the purpose of this study was to determine the effects of VGF on the retinal ganglion cells (RGCs) of mice in the optic nerve crush (ONC) model, rat-derived primary cultured RGCs and human induced pluripotent stem cells (iPSCs)-derived RGCs. The mRNA and protein ofVgf were upregulated after the ONC. Immunostaining showed that the VGF was located in glial cells including Müller glia and astrocytes but not in the retinal neurons and their axons. AQEE-30, a VGF peptide, suppressed the loss of RGCs induced by the ONC, and it increased survival rat-derived RGCs and promoted the outgrowth of neurites of rat and human iPSCs derived RGCsin vitro . These findings indicate that VGF plays important roles in neuronal degeneration and has protective effects against the ONC on RGCs. Thus, VGF should be considered as a treatment of RGCs degeneration.